A clinical study with changes in microbiological flora in chronic rhinosinusitis - Nainsi Gupta,; Adil Raza,; Rubina Galib,; Kamlesh Chandra, (Asian Journal of Medical Sciences, 2023)
Background: Chronic rhinosinusitis (CRS) is characterized by mucous membrane inflammation that lines the paranasal sinuses and nasal cavity for at least twelve consecutive weeks. Microbes play a major role in pathogenesis. The treatment objectives are to reduce mucosal edema, restore paranasal sinus ventilation, and eliminate infectious pathogens. Aims and Objectives: (1) To study the presenting clinical features of chronic sinusitis. (2) To study the changes in microbiological flora. Materials and Methods: The study was conducted on 202 patients in the Department of ENT and Microbiology (JNMCH) from December 2020 to 2022. Patients above the age of 10 years were evaluated in this study. Those who received antibiotics in the last week of the presentation and those resistant to medical therapy were excluded. Patients were subjected to a detailed history, the clinical examination, and a radiological examination. Under all aseptic precautions and after the patient’s informed consent, the sample was taken from the middle meatus area for culture and sensitivity. Results: The study had a male predominance (71.28%), with the maximum number of patients in the age group 21–30 years (38.11%). The most common clinical features were nasal obstruction (96.03%) and mucopurulent discharge (100%). The most common isolate was Staphylococcus aureus (45.13%). Conclusion: Bacterial infection is a major etiological factor in CRS. Screening for S. aureus carriers may be an alternative to decrease the infection of S.aureus. There is a statistically significant increasing trend for methicillin-resistant S. aureus (19.46%) and fungal sinusitis (13.36%).